PENGARUH USAHA KERAJINAN SERABUT KELAPA TERHADAP PENINGKATAN EKONOMI MASYARAKAT DESA TELAGA WARU KECAMATAN PERINGGABAYA KABUPATEN LOMBOK TIMUR - Ramayanto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study entitled "The Influence of Coconut Fiber Craft Business on Improving the Economy of the Community of Telaga Waru Village, Peringga Baya District" with the aim of knowing the effect of coconut fiber handicraft business (X1) on Community Economic Improvement (Y1) in Telaga Waru Village. In this study, the method used is a quantitative method with a simple linear regression approach. The samples from 273 craftsmen in Telaga Waru Village are 40 craftsmen. Sampling using probability sampling technique with random sampling, and data collection techniques using questionnaires, observation, documentation, while data analysis using SPSS 20. The results of data analysis showed that the results of the T test and determination test showed a significant influence between coconut fiber crafts on improvement of the community's economy, with a t-count value greater than t-table with a value of 7.401 > 1.685. The results of the determination test showed that the effect of coconut fiber crafts was 59.1% on improving the community's economy.